FLEXURAL STRENGTH OF LIP CHANNELS COLD-FORMED STEEL BEAM IN BACK-TO-BACK ARRANGEMENT WITH A VARIETY OF LENGTHS - Husnik Maulidya Tungga Dewi, Nindyawati (Universitas Negeri Malang, 2022)
Abstrak: Optimization of cold-formed steel construction materials in the form of merging two individual channel into built up back-to-back channel. The use of cold-formed steel is increasingly applicable with varying lengths used. Therefore, it is necessary to research the effect of variations in beam span length affect the flexural strength of cold-formed steel beams arranged back to back. This study aims to determine the load, deflection, and failure mode of back-to-back C channel beam with variations in beam span length. The research uses quantitative methods through a laboratory experimental approach. The results of the study can be concluded as follows: (1) A load of back-to-back cold-formed steel beams has decreased with an increase in the length of the beam span in each variation code test specimen. The decrease in load compared to the shortest span length of 90 cm for the lengths of 120, 210, 240 cm are 10,90%, 51,12%, and 62,39% respectively. The decrease in actual load is caused by a reduction of flexural rigidity, the presence of stress concentrations at the loading point that prevent the load from being properly distributed to the support, and the instability of the back-to-back or open sections, which increases as the length of the beam span increase. (2) Deflection of the beam due to transverse loads which act on back-to-back cold-formed steel beams increases as the span length increases for each variation code test spesimen. The beam deflection compared to the shortest span length of 90 cm for the lengths of 120, 210, and 240 cm increased by 17,26%, 73,11% dan 103,3% respectively. The decrease in beam stiffness due to increased length of the beam span with a constant spreader beam size, which results in increased distance between the loading point and the support, is what causes the rise in vertical deflection of the beam. The deflection that occurs in each length variation code exceeds the maximum deflection limit, so it is necessary to take into consideration of the load applied to the back to back cold-formed steel beam. (3) The failure modes that occured in the back-to-back cold-formed steel beam in each variation of the span length during the flexural test had the same failure, namely flange local buckling, distortional buckling, and lateral torsional buckling. The difference in failure modes among C channels in the back-to-back beam was observed and there is an interaction of local buckling, distortional, and lateral torsional buckling failure modes in one of C channel, while the other C channel only experiences lateral torsional buckling.Keywords: flexural strength, cold-formed steel, back-to-back c channel beam, variety of length